Vēḷāṇmaiyum paṇpāṭum - Kandasamy, L. S., 1939- (Tamiḻnāṭu Vēḷāṇmaip Palkalaik Kaḻakam, 1974)
On the references made to agriculture and Tamil culture in Tamil literature from the Sangam to modern times.